Headspace Solid-Phase Microextraction GCMS as a Potential In-Situ Method for the Early Detection of Fusarium Head Blight in Barley. (2nd July 2020) - Mazelin, Cassidy; Vose, Jonathan C.; Kepner, Raymond L.; Fitzgerald, Neil
Abstract: The presence of Fusarium head blight on barley impacts beer quality and can have a significant financial impact on the brewing industry. In this work we investigate the use of a portable GCMS instrument combined with a simple headspace solid phase microextraction method as a potential method for the in-situ detection of fungal growth in barley. Four volatile organic compounds (ethyl acetate, 1-pentanol, 2-pentanone, and 2-hexanone) were identified as indicators of fungal contamination. Barley samples were inoculated in-lab and tested over five days. A positive correlation between peak areas of the indicator compounds and ergosterol was obtained. The method was also applied to some naturally grown barley samples. Our preliminary results demonstrate the potential of the method as a means to determine fungal contamination in-situ.